Binge-type behavior in rats consuming trans-fat-free shortening - Wojnicki, F.H.E. (2008)
Studies from this and another laboratory involving an animal model of binge-type behavior have used vegetable shortening containing trans-fats. Due to reformulations by vegetable shortening manufacturers to remove trans-fats from their products, only trans-fat-free shortenings are now available. The goal of the present study was to assess binge-type behavior in rats with trans-fat and trans-free vegetable shortening. Trans-fat-free shortening was provided to three different groups of non-food-deprived male Sprague Dawley rats on different schedules of access: continuous access (24 hr/day — 7days/week), daily access (1 hr every day), and intermittent access (1 hr on Mondays, Wednesdays, Fridays). Trans-fat shortening was provided to a fourth group on the intermittent access schedule. A fifth group had no shortening access (chow only). Both intermittent groups (trans-fat-free and trans-fat) consumed significantly more shortening during the 1-hr period of availability than did the daily group, and there was no difference in shortening intakes between the intermittent groups. These results are identical to previous reports of binge-type behavior in rats using this model. Thus, binge-type behavior in the present behavioral model depends upon the schedule of access, not the presence of trans fats in the shortening.